2019
DOI: 10.1038/s41598-019-53867-y
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin reverses maladaptive remodeling of the aged heart through Wnt-signaling

Abstract: Healthy aging results in cardiac structural and electrical remodeling that increases susceptibility to cardiovascular diseases. Relaxin, an insulin-like hormone, suppresses atrial fibrillation, inflammation and fibrosis in aged rats but the mechanisms-of-action are unknown. Here we show that relaxin treatment of aged rats reverses pathological electrical remodeling (increasing Nav1.5 expression and localization of Connexin43 to intercalated disks) by activating canonical Wnt signaling. In isolated adult ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Here, the premature impulse elicits a brief transient arrhythmia (4 beats) and a return to sinus rhythm. (iii) An example of burst pacing (4 s) which elicits a transient VF that self terminates in β-catenin and a decrease of Dikkopff protein, with β-catenin localized in the nucleus and co-localized with connexin 43 at intercalated disk (17). Although beyond the scope of this report, the interplay between RLX and Wnt signaling is an exciting topic of further research.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, the premature impulse elicits a brief transient arrhythmia (4 beats) and a return to sinus rhythm. (iii) An example of burst pacing (4 s) which elicits a transient VF that self terminates in β-catenin and a decrease of Dikkopff protein, with β-catenin localized in the nucleus and co-localized with connexin 43 at intercalated disk (17). Although beyond the scope of this report, the interplay between RLX and Wnt signaling is an exciting topic of further research.…”
Section: Discussionmentioning
confidence: 95%
“…Frozen sections (5µm thick) were stained with Mason's Trichrome (not shown) and Rabbit anit-β-catenin antibody. The right bronchus was ligated, and the right lung was stored at −80 • C. β-catenin was analyzed using background subtraction in ImageJ (applied equally to each image using the same background subtraction), followed by an analysis of antibody fluorescence only at intercalated disk (12,17). Statistical analysis was performed by ANOVA (GraphPad Prism) followed by Tukey post-test comparisons among groups within each data set.…”
Section: Methodsmentioning
confidence: 99%
“…DCM, as one of the major complications of diabetes mellitus, is an important origin leading to high incidence and mortality of diabetes-related cardiovascular diseases ( Zamora and Villena, 2019 ). Myocardial fibrosis is a well-established cause and key factor for the increased myocardial stiffness and subsequent diastolic dysfunction in the diabetic patients ( Hu et al., 2017 ; Parim et al., 2019 ).It has been found that aging participates in the mechanism of cardiovascular remodeling ( Lakatta and Levy, 2003 ), including myocardial fibrosis and electrophysiological remodeling ( Swynghedauw, 1999 ; Martin et al., 2019 ). HUA and others have found that ROS accumulation was achieved as myocardial cell aging, leading to myocardial remodeling ( Hua et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in various in vitro models of Wnt signaling activation to explore its mechanistic and potential therapeutics benefits 120 . CHIR99021 has been shown to promote remodeling of lung and cardiac tissues after injury 121,122 . In vitro, CHIR99021 can promote de novo formation of hair follicles 123 , and maintain self-renewal of mouse intestine LRG5+ intestine SC 124 .…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%